Problem-based learning in Islamic Education subject to build students’ morals in online learning (pandemic experiences) - Andit Triono; Suci Irma Aflachah; Nur Hidayah; M. Imadul Iman Al-Qowim; Andita Radianti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Moral education as one of the critical elements in the educational process for students must be carried out under all circumstances. When there is sufficient technological infrastructure in place, online education is one of the most logical options during a pandemic.  Educators must prepare learning steps as the correct strategy for learning when implementing online learning, including those who teach Islamic Education.  Therefore, a systematic literature review employing the PRISMA Protocol was conducted for this study. Two objectives are presented: how online learning during a pandemic can be carried out, and how problem-based learning strategies can be used to influence students' morals in the context of online learning during a pandemic. The results of this study indicate that, in the context of a pandemic, educators must first prepare themselves for the online learning process, beginning with a comprehension of learning management system or internet-based education sites and progressing to the development of learning strategies. Second, educators can take advantage of problem-based learning which is operationally simple to implement during the pandemic, to shape the students’ morals. The author recommends further research on the implementation of PBL for fostering students' critical thinking in Islamic Education subjects.